'Dynamic Differentiation': The Principles of CBDR-RC, Progression and Highest Possible Ambition in the Paris Agreement. Issue 2 (24th October 2016) - Voigt, Christina; Ferreira, Felipe
Abstract: The Paris Agreement has struck a careful balance between the need for ambitious and effective climate action and for fair effort sharing among parties based on differentiation. This article provides an overview of the negotiation history of differentiation and analyzes the 'dynamic differentiation' as built into the architecture of the Agreement. While being set against the normative background of the United Nations Framework Convention on Climate Change (UNFCCC), the Paris Agreement adopts a more diversified way of differential treatment among parties, approaching it in three complementary ways: firstly, on a principled basis, reflecting common but differentiated responsibilities and respective capabilities (CBDR-RC), in the light of different national circumstances; secondly, in the content of its articles, in particular on mitigation, finance and transparency; and thirdly, on the basis of the principles of progression and highest possible ambition, which represent new and dynamic aspects of differentiation. The authors argue that 'highest possible ambition' is reflective of a duty of care that states now need to exercise. It implies a due diligence standard, which requires each government to act in proportion to the risk at stake and to take all appropriate and adequate climate measures according to its responsibility and its best capabilities. By expecting parties to apply this standard at each successive preparation of nationally determined contributions (NDCs), and to progress beyond previous ones, the Paris Agreement has set up reiterative processes, an 'international normative pull' and a collective learning environment. This, in turn, creates a reflexive approach to parties' determination of effort, promoting the evolution of voluntary cooperative behaviour.